A Case of Urinary Tract Infection and Severe Sepsis Caused by Kluyvera ascorbata in a 73-Year-Old Female with a Brief Literature Review - Majd Alfreijat (Case Reports in Infectious Diseases)
Infections that are caused by Kluyvera bacteria have been previously reported in the medical literature; however, they seem to be less common. Herein, we report a case of urinary tract infection and severe sepsis caused by Kluyvera ascorbata in a 73-year-old female. We also did a brief literature review of infections caused by this organism in adults.